BUDAYA KERJA PETUGAS PEMUTAKHIRAN DATA PEMILIH DALAM PEMILUKADA DI KOTA PADANG PANJANG - Weriza Weriza; Asrinaldi Asrinaldi; Ernita Arief (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
The voter data update shows that there were still data on the TMS voters when the DPS determined in Padang Panjang City at 4,307 or 10.96% of the voters. This research was carried out with the descriptive qualitative method through in-depth interviews with various informants, namely election organizers in Padang Panjang City and Disdukcapil and campaign teams. The results of this study show that the problem of the voter list is due to PPDP Performance Culture in the voter data updating process which is seen from 6 aspects, namely (1) the responsiveness of PPDP can understand the needs of voters and not constrained population administration factors, (2) professionalism, work according to rules and has a high competence and understanding of territories, (3) productivity, can reduce voters who do not meet the requirements significantly and nil double voters in DPS (4) accountability, PPDP is ready to answer internally the process and results of updating voter data to the KPU and externally in the level of results, (5) cooperation, PPDP has collaborated with internal KPU and external KPU in voter data summary and (6) quality of service, PPDP and KPU along with their staff conduct socialization to the public for the categories of voters eligible and not eligible in the list voters. Voters registered in the voter list are de facto and de jure voters to be one solution to fulfill the comprehensive, accurate and up-to-date principles in voter data collection